The Role of Transformational Leadership and Employee Engagement in Enhancing Organizational Performance in the Public Sector of East Java - Budi Iriani Yudaningrum; Wiwit Setyo Wardani (JOURNAL KOPERASI DAN MANAJEMEN, 2026)
Purpose – This study aims to investigate the mediating role of employee engagement in the relationship between transformational leadership and organizational performance in the public sector of East Java, Indonesia. The study addresses the limited understanding of the integrated mechanism through which transformational leadership contributes to organizational performance through employees' psychological and behavioral engagement. Design/methodology/approach – This study employed a quantitative research design. Data were collected through structured questionnaires from 285 employees working across various public sector agencies in East Java, Indonesia. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to examine the direct effects of transformational leadership on employee engagement and organizational performance, as well as the mediating effect of employee engagement. Findings – The results demonstrate that transformational leadership has a significant positive direct effect on both employee engagement and organizational performance. Furthermore, employee engagement partially mediates the relationship between transformational leadership and organizational performance. These findings indicate that transformational leadership contributes to organizational performance not only directly but also by fostering stronger psychological commitment, involvement, and engagement among public sector employees. Research limitations/implications – This study is limited to public sector employees in East Java, which may constrain the generalizability of the findings to other regions or organizational contexts. The cross-sectional design also limits the ability to examine changes in leadership, employee engagement, and organizational performance over time. Future research could employ longitudinal designs, include other regions or public institutions, and examine additional mediating or moderating variables such as organizational culture, job satisfaction, psychological empowerment, or perceived organizational support. Practically, public sector managers should strengthen transformational leadership practices by inspiring employees, communicating a clear vision, providing individualized support, and creating opportunities for employee participation and involvement to enhance organizational performance. Originality/value – This study contributes to public administration and organizational behavior literature by integrating transformational leadership, employee engagement, and organizational performance within a single mediation framework. Its originality lies in demonstrating the partial mediating role of employee engagement in translating transformational leadership into improved organizational performance.